The Effectiveness and Cost Analysis of a Pilot Newborn Hearing Screening Program at a Hospital in a Low- to Middle-Income Country - Pariya Lertbussarakam; Pittayapon Pitathawatchai (Journal of International Advanced Otology)
Background: When a universal newborn hearing screening program is not feasible, particularly in the early stages of its establishment when it requires a great deal of effort and resources, a smaller scale in screening, such as a specific geographical subset or targeted group, is suggested rather than doing nothing. This study aims to pilot a newborn hearing screening program at a hospital in a low- to middle-income country and determine its effectiveness and costs in the context of a lack of qualified audiologists.